A commentary on Michael King. “The challenge of research into religion and spirituality.” Journal for the Study of Spirituality 4 (2014): 106–20 - Timmins, Fiona (2016)
King’s publication based on a key note presentation at the 2014 British Association of theStudy of Spirituality (BASS) conference, a well written and thought provoking paper, leads us toconsider the contribution of this critique of spirituality research to contemporary debates on the topicThe views expressed within the paper are important and foster debate about the validity of researchin the field of spirituality and religion. However, at the same time, this debate is reminiscent of thenegative responses sometimes expressed about research publications in this field. At the same time,it must be recognised that there is a view held that there is an extra yard stick required for researchersin this field, who can be subjected to much higher standards and expectations than other researcherssimply because of the topic and the deep seated conflicting views that advocates and critics hold.This paper considers the merits and challenges of this paper in light of this.